Analysis of The Influence of Financing, Inflation, and The Amount of Money Supply on The Profitability of Syariah Bank in Indonesia - Aulia, Nadia Putri; Nur Aisyah, Esy (Universitas Muhammadiyah Sidoarjo, 2023)
Profitability can show good company performance. Was conducted The research to determine the effect of financing, inflation, and the money supply on the profitability of Islamic banks in Indonesia. This study uses quantitative methods using secondary data. The sampling technique used in this study uses specific criteria, with the final sample result being 8 Islamic Banks registered with the Financial Services Authority in 2012-2021. The data analysis method in this study uses SPSS-25, with multiple linear regression testing tools, classical assumption testing, hypothesis testing, and determining coefficient tests. The study results show that financing variables partially do not affect the ROA profitability of Islamic banks in Indonesia. The inflation variable partly does not affect the ROA profitability of Islamic banks in Indonesia. The money supply variable also has no partial impact on the ROA profitability of Islamic banks in Indonesia. However, the financing variables, inflation, and the money supply can all affect the ROA profitability of Islamic banks in Indonesia. The effect is 31.0%, where the variables with financing, inflation, and the money supply simultaneously affect the ROA profitability of Islamic banks in Indonesia, and other variables influence the rest.